Ethno-Biomathematics for Junior High School Students' Understanding of Cell Structure: A Case Study - Muhammad Hasbi; Fitri Fitri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Biology learning at the junior high school level, particularly regarding the structure of plant cells and tissues, is often considered difficult due to its microscopic and abstract characteristics. This study intends to integrate ethnomathematics (the study of mathematical concepts in local culture and environment) as a contextual bridge to facilitate student understanding. We conducted this case study at a junior high school in Wajo Regency, using the Classroom Action Research (CAR) method with a qualitative descriptive design. The research stages include (1) identification of local ethnomathematics; (2) development of teaching materials; and (3) implementation and observation. The findings indicated that the incorporation of ethnomathematics substantially enhanced students' visualization abilities and contextual comprehension. Students more easily internalized the concept of efficient tiling (hexagonal patterns) in plant tissues after analyzing similar patterns found in flora in their surrounding environment. This approach transformed learning into a more active and meaningful one by concretizing abstract material through locally relevant mathematical objects. This study concludes that using native botanical geometric patterns is a creative strategy that shifts the paradigm of biological learning from mere memorization to contextual exploration, while simultaneously improving students' numeracy literacy.